2010
DOI: 10.2478/v10019-010-0010-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of human cell biosensor system for genotoxicity detection based on DNA damage-induced gene expression

Abstract: BackgroundHuman exposure to genotoxic agents in the environment and everyday life represents a serious health threat. Fast and reliable assessment of genotoxicity of chemicals is of main importance in the fields of new chemicals and drug development as well as in environmental monitoring. The tumor suppressor gene p21, the major downstream target gene of activated p53 which is responsible for cell cycle arrest following DNA damage, has been shown to be specifically up-regulated by genotoxic carcinogens. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 37 publications
0
19
1
Order By: Relevance
“…Recently, Zager et al . reported the development of a p21 -mediated eGFP reporter gene bioassay system for genotoxicity detection in human hepatoma HepG2 cells [ 39 ]. Challenging this, stably transformed HepG2 cells (p21HepG2GFP) by genotoxic agents with known mechanisms of action showed that this human cell biosensor system can be used for simple and fast detection of genotoxic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zager et al . reported the development of a p21 -mediated eGFP reporter gene bioassay system for genotoxicity detection in human hepatoma HepG2 cells [ 39 ]. Challenging this, stably transformed HepG2 cells (p21HepG2GFP) by genotoxic agents with known mechanisms of action showed that this human cell biosensor system can be used for simple and fast detection of genotoxic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Rider et al reported the first cell sensor that used B lymphocytes to recognize specific bacteria with the help of membrane-bound IgM antibodies32. Mammalian cell-based biosensors have a distinct advantage in reflecting cellular physiological action rather than just quantitative detection and therefore can provide insight into mechanism of action of analytes333435. More importantly, tests based on human cells rather than other cell types, are more likely to detect contaminants that can cause adverse effects in humans.…”
mentioning
confidence: 99%
“…Though prior work has examined the gross effects (e.g., viability, proliferation) of analytes on cells313637, these gross assays do not reveal more subtle effects that mask or alter particular phenotypes of interest, such as the activation of signaling pathways. Recently, methods based on the reporting of analytes by fluorescence reaction in engineered cells offer a simple and nondestructive option33343538. Living cells used as biosensors are typically produced with a constructed plasmid, in which genes that code for the bio-reporter are placed under control of a promoter that recognizes the analyte of interest.…”
mentioning
confidence: 99%
“…14 Transfusion of myeloid progenitor cells has been evaluated in an animal model of ARS, with promising results: this technique has proven effective in protecting animals exposed to lethal doses of radiation. 15 Other areas of research include the search for ways to detect genetic alterations caused by ionizing radiation based on DNA damage-induced gene expression 16 and energy metabolism. 17 Several other interesting papers on the subject of ARS were also published in 2011.…”
mentioning
confidence: 99%